Biomarkers in neurodegenerative diseases: cortisol - Batista, Patrícia (2017)
Neurodegenerative diseases are characterized by progressive loss of cognitive function, dementia, and problems with movements. Identification of biomarkers during disease process, induce to an effective and early diagnostic test for neurodegenerative diseases. These biomarkers would allow presymptomatic disease detection of disease and would be valuable for monitoring the efficacy of disease. Cortisol is a biomarker used for stress evaluation and a potential neurodegenerative disease biomarker. Objective: The aim of this paper is to review systematically the scientific literature about evaluation to cortisol biomarker in neurodegenerative diseases. Methods: Systematic literature review on Pubmed, Medline and Scopus database with the keywords "cortisol biomarkers” and "neurodegenerative diseases". It was analyzed all existing articles (between 1988 and 2015). PRISMA criteria reporting of systematic reviews and meta-analyses were applied. The inclusion criteria were: cortisol biomarkers in neurodegenerative diseases diagnosis, presenting quantitative or qualitative results. It was excluded articles outside the scope of the subject and articles with unavailable information. Results: After applying the methodology, 14 scientific articles were included in the study. So, these studies were analyzed. Conclusions: This paper review based on the contribution of cortisol biomarkers to diagnose and treat neurodegenerative diseases.